2014
DOI: 10.1373/clinchem.2013.218149
|View full text |Cite
|
Sign up to set email alerts
|

Publication and Reporting of Test Accuracy Studies Registered in ClinicalTrials.gov

Abstract: BACKGROUND:Failure to publish and selective reporting are recognized problems in the biomedical literature, but their extent in the field of diagnostic testing is unknown. We aimed to identify nonpublication and discrepancies between registered records and publications among registered test accuracy studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 24 publications
0
44
0
Order By: Relevance
“…gov or one of the WHO Primary Registries, ensures that existence of the studies can be identified. [108][109][110][111][112] This has many advantages, including avoiding overlapping or redundant studies, and allowing colleagues and potential participants to contact the study coordinators.…”
Section: Item 27 Implications For Practice Including the Intended Umentioning
confidence: 99%
“…gov or one of the WHO Primary Registries, ensures that existence of the studies can be identified. [108][109][110][111][112] This has many advantages, including avoiding overlapping or redundant studies, and allowing colleagues and potential participants to contact the study coordinators.…”
Section: Item 27 Implications For Practice Including the Intended Umentioning
confidence: 99%
“…Korevaar et al compared prospective registered diagnostic studies to the publications. They concluded that failure to publish and selective publication were prevalent in diagnostic accuracy studies but the dataset was too small to draw firm conclusions [16]. Brazelli and colleagues, however, tracked a cohort of conference abstracts and did not find evidence of publication bias in the process that occurs after abstract acceptance [17].…”
Section: Introductionmentioning
confidence: 99%
“…This requirement does not extend, however, to registration of the diagnostic test analytics used in the trials. A recent analysis of ClinicalTrials.gov revealed discrepancies between the registered diagnostic test protocols versus what was reported in the final publications in 32% of the 418 trials reviewed [32].…”
Section: Biospecimens and Biobanksmentioning
confidence: 99%